2021
DOI: 10.51362/neonatology.today/202171671115
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance In Pregnancy

Abstract: Background: Early in the COVID-19 pandemic, limited data existed regarding the safety and efficacy of the COVID-19 vaccine in pregnant women. As such, many pregnant women have reservations about receiving the COVID-19 vaccine. However, pregnant women are of particular concern as they are considered a vulnerable population due to the increased risk of severe complications from COVID-19. This study investigates the willingness of pregnant patients to receive the vaccine before and after discussion with a health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Pregnant people's receipt of the influenza vaccine in the previous year and communication with a medical professional about vaccines were associated with increased likelihood of COVID-19 vaccine acceptance. 45,52,55 In contrast, pregnant people's prior refusal of the seasonal influenza vaccine, 47,54 lack of provider counseling, 50 younger age, 45,48 African American race, 47,48,50,53,54 Hispanic ethnicity, 47,48,50,54 and low education 50 were associated with refusal of vaccination. Frequently cited concerns included safety and effectiveness of COVID-19 vaccination, fears of birth defects, unknown long-term health effects on children, and risk of pregnancy loss.…”
Section: Covid-19 Vaccine Acceptancementioning
confidence: 98%
See 1 more Smart Citation
“…Pregnant people's receipt of the influenza vaccine in the previous year and communication with a medical professional about vaccines were associated with increased likelihood of COVID-19 vaccine acceptance. 45,52,55 In contrast, pregnant people's prior refusal of the seasonal influenza vaccine, 47,54 lack of provider counseling, 50 younger age, 45,48 African American race, 47,48,50,53,54 Hispanic ethnicity, 47,48,50,54 and low education 50 were associated with refusal of vaccination. Frequently cited concerns included safety and effectiveness of COVID-19 vaccination, fears of birth defects, unknown long-term health effects on children, and risk of pregnancy loss.…”
Section: Covid-19 Vaccine Acceptancementioning
confidence: 98%
“…Eleven of the 32 (34%) studies (Figure 2) examined pregnant people's acceptance or uptake of COVID-19 vaccination. [46][47][48][49][50][51][52][53][54][55][56] Overall, COVID-19 vaccine acceptance rates ranged between 3% and 65%. Studies conducted before the COVID-19 vaccine became available in the U.S. showed that 41% 54 and 47.80% 46 of pregnant people would be interested in receiving it.…”
Section: Covid-19 Vaccine Acceptancementioning
confidence: 99%
“…Pregnant mothers (64%) completed high school and above education were ready for the COVID vaccine [0.64(0.55, 0.73, I 2 = 98.90%, P = 0.001]. From the 15 studies estimated 4,6,16,19,21,22,25,[27][28][29][30][31][32][33][34] the prevalence of COVID vaccine acceptance among educated pregnant women was reported highest (93%) 28 by Geoghegan and lowest (31%) 25 by Egloff. [Fig.…”
Section: Prevalence Of Covid Vaccine Acceptance With a Literacy Level...mentioning
confidence: 99%
“…Specifically, when compared with their non-infected pregnant counterparts, pregnant patients are threefold more likely than their infected nonpregnant counterparts to be admitted to intensive care units (ICUs) and receive ventilator support or extracorporeal membrane oxygenation (ECMO), and their mortality rate is higher in addition to the risk of obstetric complications, such as preterm birth in particular 11 13 . Given the increased risk associated with COVID-19 during pregnancy, many pregnant women have decided to accept the vaccine even though critical data on the benefits and risks in pregnant individuals have been lacking, making it imperative to include pregnant or lactating women in COVID-19 vaccine trials 14 .…”
Section: Introductionmentioning
confidence: 99%